Institutional Initiatives to Promote Teachers’ Digital Skills - Cabrera Jurado, Rubén; Ruiz Ruiz, José María (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2021)
Ensure a sufficient knowledge and use of digital skills amongst citizens requires a strong commitment by the educational system altogether with coordinated action plans by the institutions that should guarantee this right. the objective of this paper is to conduct a retrospective study on the initiatives carried out by both the european union and spain for the promotion of teachers' digital competence. therefore, a prospective study of digital technologies in education has been carried out taking into account the significant changes experienced in all spheres of society.
Keywords: digital competence; institution; teacher training; Information Society; strategies